2021
DOI: 10.1002/mrm.28740
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative anatomy mimicking slice phantoms

Abstract: To present a reproducible methodology for building an anatomy mimicking phantom with targeted T 1 and T 2 contrast for use in quantitative magnetic resonance imaging. Methods: We propose a reproducible method for creating high-resolution, quantitative slice phantoms. The phantoms are created using gels with different concentrations of NiCl 2 and MnCl 2 to achieve targeted T 1 and T 2 values. We describe a calibration method for accurately targeting anatomically realistic relaxation pairs.In addition, we develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…For future work, we plan to develop a double‐angle VENUS prescan using the same excitation pulses as the qMRI sequences that follow, to determine a global RF scaling factor. Coupled with the use of anatomy‐mimicking quantitative MRI phantoms, 70 this would offer qMRI‐ready adaptive prescan routines and help investigate the effect of standardizing calibration measurements on multicenter accuracy and agreement.…”
Section: Discussionmentioning
confidence: 99%
“…For future work, we plan to develop a double‐angle VENUS prescan using the same excitation pulses as the qMRI sequences that follow, to determine a global RF scaling factor. Coupled with the use of anatomy‐mimicking quantitative MRI phantoms, 70 this would offer qMRI‐ready adaptive prescan routines and help investigate the effect of standardizing calibration measurements on multicenter accuracy and agreement.…”
Section: Discussionmentioning
confidence: 99%
“…Toward Large-Scale Fabrication in Anatomical Dimensions. Many approaches have been developed for phantom fabrication over the years: Altermatt and colleagues presented a casted biphasic phantom based on agar and MnCl 2 with silicone molds mimicking the brain folding pattern, 19 while Gopalan and co-workers demonstrated the possibility of a partly (GM-) printed biphasic phantom based on agar and MnCl 2 as well 18,26 and later suggested breaking down the brain pattern into phantom slices. 18 With nonprintable hydrogels fully characterized for T 1 or T 2 impacts before, 16,21,23 reproducing real GM and WM relaxation times was better achieved compared to our approach.…”
Section: D Plotting Of Biphasic Anthropomorphic 3dmentioning
confidence: 99%
“…Techniques of additive manufacturing (AM) still play a minor role, as AM is merely used for the fabrication of casting molds: Yunker and co-workers have evaluated the relevance and suitability of materials for the 3D printing of MRI phantoms, while Gopalan et al 3D printed a cast that can be manually filled up with a low viscosity hydrogel for biphasic structures. , Another study suggested a 3D-printed, PLA-based shell for filling up the phantom structure in order to simulate transcranial magnetic stimulation . Other popular alternative materials are silicones, while other approaches describe the casting or printing of hydrogel phases consisting of polysaccharides such as gelatin to match the mechanical properties of brain tissue, , or their combination with polymers such as poly vinyl alcohol (PVA), or different types of silicone. ,− …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For future work, we plan to develop a double-angle VENUS prescan using the same excitation pulses as the qMRI sequences that follow, to determine a global RF scaling factor. Coupled with the use of anatomy-mimicking quantitative MRI phantoms 71 , this would offer qMRI-ready adaptive prescan routines and help investigate the effect of standardizing calibration measurements on multicenter accuracy and agreement.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%